TIM‐3 as a potential exhaustion marker in CD4+ T cells of COVID‐19 patients - Zahra Modabber (Wiley, 2021)
Abstract Background COVID‐19 causes a range of clinical symptoms from mild to critical and can be life‐threatening. Up to now, it has led to many deaths. We aimed to evaluate exhausted markers on CD4+ T cells of COVID‐19 patients. Methods In this study, we evaluated 44 patients with confirmed COVID‐19 disease and 16 healthy individuals. Patients were divided into moderate/severe and critical groups. Peripheral blood mononuclear cells (PBMCs) were isolated and stained by anti‐human CD39, PD‐1, TIM‐3, and anti‐human CD4. The percentage of each CD4+ subpopulation was calculated by flow cytometry. Furthermore, we collected clinical information and laboratory data of both control and patient groups. Results We detected overexpression of TIM‐3 on CD4+ T cells in both critical and moderate/severe patients than in healthy individuals (HIs; p < .01 and p < .0001, respectively). CD4+ TIM‐3+ CD39+ lymphocytes were significantly higher in the critical patients than in HI (p < .05). Both Patient groups showed lymphopenia in comparison with HI, but CD4+ lymphocytes did not show any significant difference between study subjects. The increased amount of C‐reactive protein, erythrocyte sedimentation rate, creatinine, blood urea nitrogen, and neutrophil count was observed in patients compared to HI. Conclusion T cell exhaustion occurs during COVID‐19 disease and TIM‐3 is the most important exhausted marker on CD4+ T cells.